Double leverage cycle, interest rate, and financial crisis - Wang, F. Albert (Journal of Financial Stability, 2022)
We view mortgage as a risky derivative of its underlying house collateral and combine no-arbitrage valuation with equilibrium valuation approaches to develop a dynamic model of leverage cycle and interest rate. This model provides a unified explanation to pro-cyclical optimism, asset prices, and leverage, and counter-cyclical volatility and interest rate. In addition, the model shows that tightening funding margin in the mortgage securities market dampens optimism, asset prices, and leverage, whereas it raises volatility and interest rate in the housing market. A double leverage cycle leads to more volatile markets and a severe leverage cycle, thus resulting in worse financial crises.